(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Annotation. Imperfect insurance legislation, lack of proper regulation and supervision of the activities and market behavior of insurance companies and intermediaries have led to the accumulation of systemic problems that need to be solved immediately in order to intensify the development of the insurance market of Ukraine. In general, all of them lead to low confidence in the companies of the insurance sector and do not allow it to develop properly. In modern conditions, the market of insurance services goes through a stage of transformation in the field of supervision and regulation in connection with the change of regulator, which became a new structural unit of the NBU – the Department of Insurance Market Supervision. Therefore, it is important to investigate what innovations the new regulator will introduce in order to eliminate those problems that hinder its development.